Techno-economic assessment of a solar PV, fuel cell, and biomass gasifier hybrid energy system - Anand Singh; Prashant Baredar (Energy Reports, 2016)
The interest of power is expanding step by step all through the world. Because of constrained measure of fossil fuel, it is vital to outline some new non-renewable energy frameworks that can diminish the reliance on ordinary energy asset. A hybrid off-grid renewable energy framework might be utilized to reduction reliance on the traditional energy assets. Advancement of crossover framework is a procedure to choose the best mix of part and there cost that can give shabby, solid and successful option energy resource. In this paper sun oriented photovoltaic, fuel cell, biomass gasifier generator set, battery backup and power conditioning unit have been simulated and optimized for educational institute, energy centre, Maulana Azad National Institute of Technology, Bhopal in the Indian state of Madhya Pradesh. The area of the study range on the guide situated of 23ê12′N latitude and 77ê24′E longitude. In this framework, the essential wellspring of power is sun based solar photovoltaic system and biomass gasifier generator set while fuel cell and batteries are utilized as reinforcement supply. HOMER simulator has been utilized to recreate off the grid and it checks the specialized and financial criteria of this hybrid energy system. The execution of every segment of this framework is dissected lastly delicate examination has been performing to enhance the mixture framework at various conditions. In view of the recreation result, it is found that the cost of energy (COE) of a biomass gasifier generator set, solar PV and fuel cell crossover energy system has been found to be 15.064 Rs/kWh and complete net present cost Rs.51,89003. The abundance power in the proposed framework is observed to be 36 kWh/year with zero rates unmet electrical burden.
Keywords: 330; Biomass gasifier; Fuel cell; HOMER; Hybrid energy system; Solar PV